Justification of The United Nations Organization’s CEDAW Charter in Ensuring Women’s Rights in Bangladesh - Huq, Naznin; Rifat-Ur-Rahman, Md. (ABC Journal of Advanced Research, 2019)
Even with the praiseworthy provisions of the Convention on the Elimination of all forms of Discrimination against Women, (CEDAW) aiming to stop discrimination against women all over the world. Still discrimination of women all over the world is in high range. The situation of Bangladesh in this regard is much worse. The existing stand of Bangladesh regarding Clause 2 and 16-1(c), has made it impossible to fully establish women’s right in the country. This paper attempted to make a case for the explanation of fully implementing CEDAW in Bangladesh, using the Constitution of Bangladesh. The Constitution of Bangladesh clearly identifies equal rights for both men and women, whereby non-ratification of two clauses of the CEDAW charter is clearly unjustifiable. Thus this paper has strengthened the case by conducting an extensive literature review of the CEDAW charter along with the state of women’s rights in the Constitution of Bangladesh. It will serve as a basis for future changes in policy development regarding the ratification of the CEDAW Charter in Bangladesh.